Is there evidence for statins in the treatment of aortic valve stenosis? - Akın, Ibrahim; Nienaber, Christoph (World journal of cardiology, 2017)
Research revealed that the pathogenesis of aortic stenosis (AS) not merely comprises of a mechanical wear and tear process yet that active biological processes, similar to those of coronary artery disease are involved, a promising role for statins in disease-modifying therapy was suggested. However, recently, many prospective studies could not observe decreased progression nor regression of the disease. Here, we review the current knowledge on the pathomechanisms of AS and its similarities and differences with atherosclerosis. Moreover, we discuss whether there is still a place for statins in the treatment of particular AS patient subgroups.
Gesehen am 11.04.2018